The Role of Life Meaning, Discrimination, and Forgiveness in the Mental Health of Criminals During Reintegration - Verma, Shashikant (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Reintroduction of ex-offenders in society is a difficult process that is usually hampered by mental health problems. With the intention of exploring the association between life meaning, forgiveness, discrimination, and the mental health of ex-offenders on reintegration, this study was designed. A survey, specifically designed for this purpose, was performed on 200 random participants selected from a pool of 1000, with the sample consisting of 60% males and 40% females. The incarceration duration reported by the participants was from 0 to 2 years for 30%, 3 to 5 years 40%, 6 to 10 years 20%, and more than 10 years 10%. Using the General Health Questionnaire-12 (GHQ-12), mental health was assessed with mean scores varying in degree of distress with (Mean = 15.8, SD = 4.3 for 3–5 years; 19.6, SD = 5.4 for 11+ years). Results show strong relationships, e.g. higher life meaning (r = -0.30), forgiveness (r = -0.35), and negative mental health distress correlation; while discrimination (r = 0.50) has strong positive relationship with distress. Further, community support moderated and was significant with lower mental health scores among individuals who reported greater community support (Mean = 11.1). Descriptive statistics, correlation analyses and cross comparisons of different levels of incarceration and community support were used as methodology. This could indicate that focusing on psychological indicators such as self-forgiveness and meaning (life) while combating discrimination could have a positive impact on the mental health and overall success of reintegration of ex-offender. Future research should specifically examine the development of such interventions that might improve well being and social integration of all formerly incarcerated people.